Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia - Li, Fengyuan; Li, Shuqiang; Jäger, Peter (Zootaxa, 2014)
Five new Althepus species and one new Psiloderces species of the family Ochyroceratidae are described from Southeast Asia: Althepus erectus spec. nov. (male) and A. nophaseudi spec. nov. (male, female) from Laos, A. flabellaris spec. nov. (male, female) from Thailand, A. reduncus spec. nov. (male) from Myanmar, A. spiralis spec. nov. (male) from Malaysia, and Psiloderces dicellocerus spec. nov. (male) from Indonesia. Primary types are deposited in the Senckenberg Research Institute in Frankfurt, Germany (SMF).